The relationships between crystallization characteristics and heat sealing properties of high-density polyethylene films. (January 2014) - Miyata, Ken; Ozama, Taku; Nishioka, Akihiro; Koda, Tomonori; Murasawa, Go
The relationships between crystallization characteristics and heat sealing properties of high-density polyethylene (HDPE) films were determined. HDPE with a 1.1 g/10 min melt flow index (MFI) (190℃, 2.16 kg) was melt mixed in a twin-screw extruder with a 0.04 g/10 min MFI HDPE. The high molecular weight HDPE (HMW HDPE) concentration was varied between 1 and 20 wt%. The HDPE blends were cast into a 50 µm thick film. The films were heat sealed at 125℃ and 128℃. The seal bar pressure was kept constant at 0.13 MPa. The heat seal time was varied from 0.5 to 2.0 s. Heat-sealed strength was measured by T-peel test. The molecular structure development during the heat seal process was evaluated by differential scanning calorimeter and wide-angle X-ray diffraction. The HMW HDPE decreased the film heat seal strength when sealed at 125℃. However, at 128℃ the presence of up to 10 wt% reduced the heat sealing time.